Evaluation of Steel Industrial Slag as Partial Replacement of Cement in Concrete - Affan Jalil; Anwar Khitab; Hamza Ishtiaq; Syed Hassan Bukhari; Muhammad Tausif Arshad; Waqas Anwar (Civil Engineering Journal, 2019)
Cement is the most important ingredient in concrete, which acts as a binding material. It is evaluated that cement is the second largest industrial source of CO2 on earth. This demands a partial or full replacement of cement by an environment-friendly material. In this research industrial waste slag from a local Steel Mill, namely Mangla Metals was selected as possible replacement of cement. Some preliminary standard tests conducted on the slag showed its strong chances to be used as pozzolana. Slag used for this study was reduced to the particle size passing through ASTM standard sieve #100. Concrete specimens containing 10% and 20% replacement of cement by slag were prepared. The mechanical properties like compressive, split cylinder tensile and flexure strength were determined as per standard ASTM methods. Tests were conducted at 3, 7 and 28 days of concrete age. Results show a decrease of 14% in compressive strength, 7.5% in tensile strength and 10.5% in flexure strength for 10% replacement vis-à-vis control specimens at 28 days. For 20% replacement, the decrease in compressive, tensile and flexure strength are 25.5%, 29%, 31% respectively. Additionally, ASTM standard strength activity index test with finer slag particles passing through ASTM sieve #200 provided compressive strength more than that of control specimen. Based on the results, it is concluded that the industrial slag has the potential to partially replace the cement if slag is ground to the particles, passing through ASTM sieve #200. This could lead to a huge reduction of cement quantity in concrete and the environmental burden due to deposition of waste slag in landfills.